2006
DOI: 10.1158/0008-5472.can-05-3577
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Mitogen-Activated Protein Kinase Function in Xenograft Models of Prostate Cancer

Abstract: Mitogen-activated protein kinases (MAPK) play important roles in malignancy. The ability to detect and quantitate MAPKs in live animal models of cancer will facilitate an understanding of disease progression. We have developed a gene expression-based imaging system that detects and quantifies MAPK activity in prostate cancer tumors implanted into severe combined immunodeficient mice. The imaging technology uses a modified version of two-step transcriptional amplification (TSTA). The tissue specificity of gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Downstream of EGFR, MAPK/Erk1/2 activation is the key event to drive proliferation, and similar to constitutively active EGFR, an increase in constitutive activation of MAPK/ Erk1/2 signaling has also been reported in human PCA as it progresses to a more advanced and androgen-independent malignancy (24). Furthermore, some studies have also shown that MAPK/Erk1/2 is constitutively active in DU145 cells, and that Erk1/2 kinase activity decides activation of transcription factors for cell proliferation (8)(9)(10).…”
Section: Discussionmentioning
confidence: 93%
“…Downstream of EGFR, MAPK/Erk1/2 activation is the key event to drive proliferation, and similar to constitutively active EGFR, an increase in constitutive activation of MAPK/ Erk1/2 signaling has also been reported in human PCA as it progresses to a more advanced and androgen-independent malignancy (24). Furthermore, some studies have also shown that MAPK/Erk1/2 is constitutively active in DU145 cells, and that Erk1/2 kinase activity decides activation of transcription factors for cell proliferation (8)(9)(10).…”
Section: Discussionmentioning
confidence: 93%
“…To circumvent these difficulties, in the current study we used in vivo biophotonic imaging technology (IVIS, Xenogen Corp.) that allows monitoring cell survival in vivo within the living animal in a real-time fashion (7,33). IVIS has already been applied for the spatial and temporal detection of cancer cells during drug and gene therapy (13,14,24,42,48) to follow the survival and biodistribution of cell transplants (20,21,40,47) or expression of viral genes (35). We further improved this technique by combining it with retroviral overexpression of the firefly luciferase in the MSC to be injected.…”
Section: Introductionmentioning
confidence: 99%
“…A significant barrier to targeted expression of a reporter is the relatively weak activity of cellular promoters. One strategy to overcome this obstacle is two‐step transcriptional amplification (TSTA) (40). The basis of TSTA is using weak cellular promoters to express a potent transcriptional activator.…”
Section: Further Development Of Pet Reporter Imaging Systems For Precmentioning
confidence: 99%